Uranium-thorium mineralization and albitization - El Sokkary A. A. (Acta mineralogica-petrographica, 1982)
This work sheds some light on the relation between albite-bearing or alkaline rocks and U—Th anomaly. Various local and international examples are given. The chemical basis for this association is briefly outlined. Rocks tending to show a trend of albitization or a trend of alkalinity should receive intensive prospection program for U and Th.